The Protective Effects of Perch Essence Against Muscle Atrophy in Cancer Cachexia and Cisplatin Treatment - Shu-Lan Yeh; Pei-Yin Chen; Jiunn-Wang Liao; Ruo-Li Huang; Shu-Han Yu; Ling-Ni Chen; Mao-Hsiang Lee; Li-Wen Chen; Haw-Wen Chen; Ya-Chen Yang; Yu-Ling Wu; Kai-Li Liu (Current Issues in Molecular Biology)
Muscle atrophy, through several pathways including increased protein catabolism, leads to adverse effects in cachexia induced by cancer and chemotherapy. Perch essence (PE) is a perch extract rich in branched-chain amino acids and peptides. The present study initially investigated the effects of PE supplementation on muscle atrophy in a mouse model of cancer cachexia induced by C26 cancer cells and compared these effects with those of tryptone. Compared with the tumor-only group, we found that PE supplementation significantly improved body weight, muscle mass, maximum limb grip strength (MLGS), and myosin heavy chain expression in the muscles of tumor-bearing mice. PE also significantly inhibited the expression of factors related to protein degradation, oxidative stress, and inflammation, while enhancing the expression of antioxidant enzymes in tumor-bearing mice. These effects of PE were associated with an increased expression of phosphorylated Akt and forkhead box protein O1, along with a reduced expression of phosphorylated nuclear factor-κB p65 in the muscles of tumor-bearing mice. Furthermore, PE similarly increased MLGS and attenuated muscle atrophy in mice exposed to cisplatin by inhibiting protein degradation. All the therapeutic effects of PE supplementation mentioned above were generally greater than those of tryptone supplementation. These results suggest the potential of PE in protecting against muscle atrophy induced by tumors or chemotherapy.